Weiß der Verbraucher wirklich, welche Qualität er kauft?: Eine Studie zur Qualitätserwartung an Prüfzeichen; Does the Consumer Really Knows which Quality he Buys? A Study about the Expected Quality from Quality Labels - Sabine Kubitzki; Stephanie Krischik-Bautz (German Journal of Agricultural Economics (GJAE), 2011)
– Quality labels for food products are an important consumer policy tool and are used for product diversification strategies by the producers. In the literature, the effectiveness of such labels concerning the purchase behaviour of consumers has been doubted. In this context, our paper compares the guaranteed quality of three labels - QS, CMA and BIO - with their expected quality by the consumer. The QS label and particularly the BIO label are process-orientated and characterized by a high level of control and sanctions. The CMA label assured, till its termination in 2009, a specific sensory quality accompanied with less rigorous mechanisms of control and sanctions. The results of a representative online survey indicate that consumers expect the same quality level from the CMA label and the QS label, although, in fact, QS guarantees a higher process quality. The CMA label can differentiate from the others in consumers' perception as a regional origin label, whereas the BIO label stands out for the material dimension of quality including safety and quality items. To conclude, the perception of the material quality of labels (e.g. CMA label) can be biased by positively valued ideational product attributes. Thus, it is supposable that the consumer assesses the quality better than it actually is.
Keywords: 330; Produktinformation; Produktqualität; Konsumentenverhalten; Deutschland